Kaifiyyat Ikhtibār Kafā’ah al-Kalām fī Taʻlīm al-Lugah al-ʻArabiyyah - Ibnu Masud Luthfi (Al-Fusha : Arabic Language Education Journal, 2021)
Each Arabic language competency has different ways of conducting tests to measure students' language skills, especially mahārah al-kalām which nota bene measures the ability to produce Arabic orally. This article aimed to develop mahārah al-kalām test formulation in the field of Arabic language learning. Researcher used qualitative methods to discuss mahārah al-kalām test from various sources. The data showed that the content of the test was related to the ability to pronounce Arabic sounds, grammar, vocabulary, fluency, and understanding, each of which had detailed criteria to be the background for the preparation of mahārah al-kalām test material. The language component is needed to emphasize the importance of the ability to communicate spoken Arabic correctly.